18-Year-old who attempted suicide by ingesting 300 mg of vortioxetine: A case report - Hachem, Shaha (2022)
Vortioxetine is a novel antidepressant and atypical antipsychotic that does not fit in to the established classes of Selective Serotonin Release In- hibitors (SSRIs), tricyclic antidepressants, nor monoamine oxidase inhi- bition...